2007
DOI: 10.1007/s11207-007-9061-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient Coronal Sigmoids and Rotating Erupting Flux Ropes

Abstract: To determine the relationship between transient coronal (soft X-ray or EUV) sigmoids and erupting flux ropes, we analyse four events in which a transient sigmoid could be associated with a filament whose apex rotates upon eruption and two further events in which the two phenomena were spatially but not temporally coincident. We find the helicity sign of the erupting field and the direction of filament rotation to be consistent with the conversion of twist into writhe under the ideal MHD constraint of helicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
182
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(205 citation statements)
references
References 69 publications
22
182
1
Order By: Relevance
“…4.2). This difference between the PIL on the Sun and the MC axial direction can be explained by a counter-clockwise rotation of the ejected flux rope, as expected, since its helicity is negative (Török & Kliem 2005;Green et al 2007).…”
Section: Searching For the Solar Sourcesupporting
confidence: 70%
“…4.2). This difference between the PIL on the Sun and the MC axial direction can be explained by a counter-clockwise rotation of the ejected flux rope, as expected, since its helicity is negative (Török & Kliem 2005;Green et al 2007).…”
Section: Searching For the Solar Sourcesupporting
confidence: 70%
“…This could be due to the fact that the time scale of the rotation of these filaments is smaller than the cadence of our data. In an independent study using TRACE data Green et al (2007) studied 7 active region filaments which rotated during eruption. In their study, four events were failed eruptions.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the ejected helicity is provided by the twist in the sub-photospheric part of the magnetic flux tube forming the active region. Green et al (2007) found the helicity sign of the erupting field and the direction of Solar magnetic fields and helicity 185 filament rotation to be consistent with the conversion of twist into writhe under the ideal MHD constraint of helicity conservation. For positive (negative) helicity the filament apex rotates clockwise (counterclockwise), consistent with the flux rope taking on a reverse (forward) S shape, which is opposite to that observed for the sigmoid.…”
Section: H Zhangmentioning
confidence: 59%